2020
DOI: 10.1016/s2215-0366(19)30298-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiology research: delivering evidence about drug safety and effectiveness in mental health

Abstract: There is a need for research that provides an evidence base for the pharmacotherapy of people with mental disorders. The abundance of digital data in recent years has facilitated pharmacoepidemiology in the form of observational comparative effectiveness studies at the population level. Advantages are large patient samples, coverage of under-researched sub-populations and naturalistic conditions. Pharmacoepidemiology is also cheaper and quicker to carry out than RCTs, meaning that issues regarding generic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Indeed, in line with rapid developments in data resources and analytical techniques, many guidelines are now beginning to include evidence from robust observational pharmacoepidemiological studies alongside RCTs. 13 But even more important are the n=1 trials, for these are the core of medical practice since every time a medicine is prescribed an n=1 experiment is being conducted. In some patients the experiment works and in others it fails, the patient either does not respond or the adverse effects outweigh the therapeutic benefit.…”
Section: Concerns About Perceived Lack Of Evidencementioning
confidence: 99%
“…Indeed, in line with rapid developments in data resources and analytical techniques, many guidelines are now beginning to include evidence from robust observational pharmacoepidemiological studies alongside RCTs. 13 But even more important are the n=1 trials, for these are the core of medical practice since every time a medicine is prescribed an n=1 experiment is being conducted. In some patients the experiment works and in others it fails, the patient either does not respond or the adverse effects outweigh the therapeutic benefit.…”
Section: Concerns About Perceived Lack Of Evidencementioning
confidence: 99%
“…Ia: evidence from meta-analysis of randomised controlled trials (RCTs) Ib: evidence from at least one RCT IIa: evidence from at least one controlled study without randomisation IIb: evidence from at least one other type of quasi-experimental study III: evidence from non-experimental descriptive studies, such as comparative studies, correlation studies and case-control studies IV: evidence from expert committee reports or opinions and/ or clinical experience of respected authorities This categorisation is most appropriate for questions of short-term efficacy. Similar taxonomies for other types of research question, including long-term impacts and real-world effectiveness, do not yet exist (Davis et al, 2019) and the following is proposed.…”
Section: Categories Of Evidence For Causal Relationships and Treatmentmentioning
confidence: 99%
“…The evidence needed by clinicians and patients with dementia will almost certainly require the inclusion of observational studies in the evidence base, as reflected here. 23 Observational research has inherent problems with confounding; thus a strength of this review is that it specified all observational trials needed to adjust for the main confounder of vascular risk, and it used an established tool to assess the quality of observational studies. 27,43 Even with a wide range of study types allowed, few studies were found, and none directly addressed the question.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Therefore, it is important at least to consider whether observational research can add to the evidence. 23 This review aims to investigate the wider health effects of statins compared with no pharmacologic lipid management in people older than 65 years with any type of dementia, with the primary outcome the reduction of MACE, by reviewing trials and observational research.…”
Section: Introductionmentioning
confidence: 99%